2012
DOI: 10.3233/jbr-2011-023
|View full text |Cite
|
Sign up to set email alerts
|

Phyllometry and carpometry, chemical and functional characterization of fruits of Sorbus domestica L. (service tree) selections

Abstract: Service tree (Sorbus domestica L.) belongs to a large genus of plants, that in the past characterized the agricultural landscape of large areas of Europe. In the light of recent acquisitions regarding nutraceutical and functional properties of service fruits in allied Sorbus species, our work aimed at the morphological description, evaluation of fruit quality and functionalnutraceutical properties of the same accessions selected for timber, in order to identify double aptitude plants. Morphological and chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 13 publications
3
17
1
2
Order By: Relevance
“…The limited published data regarding the antioxidant potential of S. domestica fruits (Termentzi et al 2006;Egea et al 2010;Piagnanini et al 2012) indicate that they possess a moderate antiradical capacity toward DPPH • and • NO, which is in reasonable agreement with the results obtained herein. Also, Termentzi et al (2006) demonstrated higher antioxidant activity of methanol extracts compared to water extracts, as we also confirmed.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The limited published data regarding the antioxidant potential of S. domestica fruits (Termentzi et al 2006;Egea et al 2010;Piagnanini et al 2012) indicate that they possess a moderate antiradical capacity toward DPPH • and • NO, which is in reasonable agreement with the results obtained herein. Also, Termentzi et al (2006) demonstrated higher antioxidant activity of methanol extracts compared to water extracts, as we also confirmed.…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, the work of other investigators indicates S. domestica fruits to be a valuable source of chlorogenic acid (Forino et al 2015), whereas it was not identified in the present study. Similarly, gallic acid was previously detected in fruits of S. domestica (Piagnanini et al 2012), but it was not quantified in the present study. The listed differences between authors in regard to phenolic profiles could be affected by various factors apart from experimental conditions, such as the stage of fruit maturity, genetic factors, environmental considerations and stress (Pandey & Rizvi 2009).…”
Section: Resultssupporting
confidence: 40%
See 1 more Smart Citation
“…Edible fruits characterizing this species make it an ideal model for the determination and further analysis of morphological and chemical diversity of populations. To date, only several studies of the morphological characteristics [ 18 , 19 , 20 , 21 , 22 ] and/or chemical composition [ 23 , 24 , 25 , 26 , 27 ] of the fruits have been carried out on the service tree. The fruit’s chemical composition was studied by different analyses including total phenols, flavonoids and tannins, macro- and micro-elements, and determination of antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their good discriminatory potential, fruit descriptors have only been successfully used in a few cases compared to leaves, probably because of their relatively short presence on the plant. For example, fruit descriptors have been used to characterize cultivars in fig (Ficus carica L.) [22], olive (Olea europaea L.) [23], sweet cherry (Prunus avium L.) [24], and Sorbus domestica L. [25]. In our experience, white mulberry fruits may vary greatly in color, size, and shape among cultivars, suggesting good discriminatory potential.…”
Section: Introductionmentioning
confidence: 84%